PENGARUH PELAKSANAAN PEMBELAJARAN DARING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V DI SDN NO. 30 KASSI KABUPATEN JENEPONTO - ., Rosdiana; Haris, Hajrah; Basam, Fajri (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to 1) describe the implementation of online learning on the learning outcomes of fifth grade students at SDN No. 30 Kassi Jeneponto Regency 2) Describe the Effect of Online Learning Implementation on the Learning Outcomes of Class V Students at SDN No. 30 Kassi Jeneponto Regency. This research is an expost facto quantitative research with a simple linear regression research design. This research was conducted at SDN No. 30 Kassi Jeneponto Regency. The population in this study amounted to 37 students and the sample amounted to 37 students. The instrument used was a questionnaire in managing data, analyzed using descriptive analysis and inferential analysis. Based on the results of data analysis, the conclusions obtained are, 1) the implementation of online learning for fifth grade students at SDN No. 30 Kassi, Jeneponto Regency, has been carried out moderatly. 2) learning outcomes of fifth graders at SDN No. 30 Kassi Jeneponto district, is in the mdium category 3) There is a positive influence on the learning outcomes of fifth graders at SDN No. 30 Kassi Jeneponto Regency, shows that the online learning variable has a positive coefficient value of 0.212, has a t-count value of 2.351> t-table 2.028, and a significant value of 0.024 <0.05.). This means that the online learning variable has a positive and significant effect on learning outcomes. Proving that H_0 is rejected and H_a is accepted. And the contribution of the influence of the implementation of online learning on the learning outcomes of the fifth grade students of SDN No. 30 Kassi Jeneponto Regency that is equal to 63.6% while the rest is influenced by other variables. The implications of this research can be seen that the implementation of online learning for fifth grade students at SDN No. 30 Kassi Regency has a positive influence, it is quite good, so it needs to be improved so that in the future all fifth grade students will not only be dominated by a few people, but all students will be able to get higher achievements both in terms of cognitive.